Efeito da pressão na obtenção e nas propriedades óticas e sensoras de filmes finos à base de 'SN''O IND. 2' com a adição de 'ZNO' - Berger, Danielle [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In this work thin films of SnO2 with addition of ZnO using 1% mol, 1,5% mol and 2% mol deposited in Si substrate by spin coating were obtained. A study by different thermal treatment at 330°c for 32h was realized after obtaining crystalline phase at 550°C for 2h. The thermal treatment in thin films at 330°c for 32h in a furnace conventional and in a furnace under pressure of 2MPa was compared to the optical and sensor properties. For the thin films thermically treated at 330°c for 32h in normal conditions of the atmospheric pressure it was observed that when we add ZnO in SnO2 the grain size decrease from 8nm (± 3 nm) para 6nm (± 3 nm). However for the thin films thermically treated under pressure of 2MPa in air there was an increase in the grain size. In the thin films of SnO2 and ZnO the thermal treatment at 330°c for 32h under pressure of 2 MPa in air has a great influence in the thickness and the grain size. The thin films crystallize in tetragonal phase cassiterite to SnO2 and crystallize in hexagonal wurtzite phase zincite to ZnO. In the thin films SnO2 + 1% mol ZnO, SnO2 + 1,5% mol ZnO and SnO2 + 2% mol ZnO the thermal treatment at 330°C for 32h under pressure of 2MPa in air the second phase of the Zn2SnO4 appears as a consequence of a minor solubility of ZnO in the SnO2. The optical properties of photoluminescence show the thermal treatment at 330°c for 32h under pressure of 2MPa in air leads to a violet shift where shallow defects are predominantly in this region like oxygen vacancies. For the thin films with ZnO addicted there is a tendency to increase the Egap and major structure ordering. In the sensor properties was obtained a better response to hydrogen gas (H2) for the ZnO thin films thermically treated at 330°c for 32h under pressure of 2 MPa in air there is an increase the specific surface area to adsorption and desorption reaction with H2 gas.

Neste trabalho foram obtidos filmes finos de SnO2 com adição de ZnO (1% mol; 1,5% mol; 2% mol) depositados por spin coating. Foi realizado estudo pela diferença do tratamento térmico a 330°C por 32h após obtenção de fase cristalina a 550°C por 2h. O tratamento térmico dos filmes finos a 330°C por 32h em forno convencional e em forno sob pressão de 2MPa em ar foi comparado quanto a suas propriedades óticas e sensoras. Para filmes finos tratados termicamente a 330°c por 32h observou-se que a adição de ZnO tem influência no tamanho de grão de 8nm (± 3 nm) para 6nm (± 3 nm). Entretanto para os filmes finos sob pressão de 2 MPa em ar há um aumento do tamanho de grão. Nos filmes finos de SnO2 e ZnO o tratamento térmico a 330°c por 32hsob pressão de 2 MPa em ar tem grande influência no tamanho de grão e na espessura. Obteve-se fase cristalina tetragonal cassiterita para SnO2 e fase cristalina hexagonal wurtzita zincita para ZnO. Nos filmes finos de SnO2 + 1,5% em mol de ZnO e SnO2 + 2% em mol de ZnO o tratamento térmico a 330°C por 32h sob pressão de 2 MPa em ar aparece uma fase secundária de Zn2SnO4 como consequência de menor solubilidade de ZnO em SnO2. As propriedades óticas de fotoluminescência indicaram que o tratamento térmico a 330°C por 32h sob pressão de 2 MPa em ar leva a um deslocamento para a região em menores comprimento de onda (violeta) onde predominam defeitos rasos como vacâncias de oxigênio. Para os filmes finos com adição de ZnO há uma tendência ao aumento do Egap e maior ordenamento da estrutura. Nas propriedades sensoras obteve-se melhor resposta do gás hidrogênio (H2) para o filme fino de ZnO tratado termicamente a 330°c por 32h sob pressão de 2 MPa em ar onde há aumento de área superficial específica para reações de adsorção e dessorção do gás H2.
Keywords: Físico-química; Filmes finos; Fotoluminescencia; Gás; Detectores; Photoluminescence